OP65 An Overview Of Participatory Approaches, Stakeholders, Methods, Topics and Challenges In Medical Device Development: A Scoping Review. (23rd December 2022) - Woudstra, Kas; Reuzel, Rob; Rovers, Maroeska; Tummers, Marcia
Abstract : Introduction: Stakeholder involvement in medical device development draws much attention. To make well-considered methodological choices while involving stakeholders, it is essential to know what approaches are available and what challenges they bring in practice. Therefore, the aim of this review was to study which participatory approaches are used in the early stages of the lifecycle of medical device development, and to describe the most important characteristics of these approaches. Methods: We conducted a scoping review and searched PubMed, Embase and Web of Science for articles published between July 2014 – July 2019. Papers were included if they presented original research featuring any form of stakeholder participation in the development of medical devices. We used The Spectrum of Public Participation to categorise the approach of each paper. We describe four characteristics of each approach: the stakeholders involved, data-collection methods, topics addressed, and the challenges associated with the approaches as perceived by the researchers. Results: From the 14, 838 papers from the initial search, 278 were included. All papers could be categorized into three levels of participation: collaboration, involvement, and consultation. The results show that patients and healthcare professionals are most frequently engaged in all approaches, besides stakeholders like citizens, relatives, and experts. The most often used data-collection methods are workshops in the collaboration approach, and interviews in the involvement and consultation approach. Topics addressed in all approaches are: the initial problem, requirements of devices, design choices, testing of devices, and procedural aspects of the involvement. Challenges in the approaches are related to sampling, analysis, social dynamics, feasibility, and closure. Conclusions: This review shows that despite the abundance of methods mentioned in literature, there are three main approaches to involving stakeholders in device development: collaboration, involvement, and consultation. These mainly differ in the degree of power that is granted to stakeholders, but are comparable in terms of data-collection methods, stakeholders, topics, and challenges.